Pelatihan Aplikasi G-Develop Bagi Guru PAUD di Kota Ponorogo Untuk Memfasilitasi Pembuatan Games Pembelajaran Anak Usia Dini - Muhibuddin Fadhli; Prihma Sinta Utami (Community: Jurnal Pengabdian Kepada Masyarakat, 2021)
Creating an instructional media is an aspect that should be mastered by the teacher. The disruption era has forced the teacher behavior they have to adapt to plan and create an instructional media. This training aims bridging between the needs of the disruption of era and teacher skills in developing ICT-based instructional media. G-Develop software uses in this training because this app does not need a script and very easy to use, this app only uses a drag and drop tool. This training was followed by 40 early childhood teachers from Ponorogo District. The target for this training is 70% participants can produce a “fruit match” app form this software. From the data result and the evaluation on the end of the training shows 71% participants can use and make a game for their students